Towards An Intelligent Arabic-Speaking Tool For Dyslexia Screening Using Natural language Processing - Mahmoud, GUENDOUZ; BENSATTALAH, AISSA; Bendjakhdel, SAAD Elhadj (Journal of Ecohumanism, 2025)
Reading is a fundamental skill for children and is crucial to their educational development. However, this development is not always smooth and simple. Some children exhibit specific difficulties known as reading disorders. These disorders vary from case to case; they can range from severe conditions such as dyslexia to less severe forms of learning difficulties, affecting a child’s ability to read fluently and comprehend text. In this paper, we proposed anArabic-speaking Tool for Dyslexia Screening based on Natural Language Processing (NLP) and Artificial Intelligence (AI) for problems detecting of Dyslexia in children and for accurate test to measure the student’s reading performance.